2010
DOI: 10.1021/ol9028918
|View full text |Cite
|
Sign up to set email alerts
|

Arylchlorogermanes/TBAF/“Moist” Toluene: A Promising Combination for Pd-Catalyzed Germyl-Stille Cross-Coupling

Abstract: The trichlorophenyl,-dichlorodiphenyl,-and chlorotriphenylgermanes undergo Pd-catalyzed crosscouplings with aryl bromides and iodides in the presence of TBAF in toluene with addition of the measured amount of water. One chloride ligand on the Ge center allows efficient activation by fluoride to promote transfer of one, two or three phenyl groups from the organogermane precursors.The Pd-catalyzed cross-coupling of organogermanes has thus far received much less attention 1 than the couplings involving organostan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…The yield increased when couplings were performed with addition of a measured amount of water (µ1030 equiv; Entries 68), as observed before for couplings with chloro(phenyl)germanes. 16,17 The SbF 5 /TBAF combination in moist toluene allowed transfer of two phenyl groups from germane 2, as expected based on the couplings of Ph 2 GeCl 2 with aryl halides promoted by TBAF. 17 One-pot treatment of germanes 1, 2, or 3 with SbF 5 /C followed by Pd-catalyzed (TBAF/moist toluene) reactions with 1, 2, or 3 equiv of aryl halides, respectively afforded various biaryls 7b7d in good yields and regioselectivity (Table 4).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The yield increased when couplings were performed with addition of a measured amount of water (µ1030 equiv; Entries 68), as observed before for couplings with chloro(phenyl)germanes. 16,17 The SbF 5 /TBAF combination in moist toluene allowed transfer of two phenyl groups from germane 2, as expected based on the couplings of Ph 2 GeCl 2 with aryl halides promoted by TBAF. 17 One-pot treatment of germanes 1, 2, or 3 with SbF 5 /C followed by Pd-catalyzed (TBAF/moist toluene) reactions with 1, 2, or 3 equiv of aryl halides, respectively afforded various biaryls 7b7d in good yields and regioselectivity (Table 4).…”
supporting
confidence: 55%
“…One chloride ligand on the Ge center is sufficient to allow efficient activation by fluoride and subsequent transfer of one, two or three phenyl groups from the organogermane precursors. 16,17 We showed that arylchlorogermanes can render a coupling efficiency comparable to that of the more established stannane and silane counterparts and that their coupling efficiency reflected their ability to generate reactive hypervalent intermediates upon fluoride activation. 17 Hiyama and co-workers utilized tri-, di-, and monoallyl(aryl)-silanes in Pd-coupling with aryl halides to access biaryls.…”
mentioning
confidence: 97%
“…During the optimization of the cross-coupling reactions between chlorogermanes and 1-iodonaphthalene (see Table 2) it became obvious that the outcome of the couplings strongly depended on TBAF/organogermanes ratios 22. TBAF most likely facilitates coupling by generating the more reactive hypervalent fluorogermanium species and the reactivity of these species could be superior in toluene solvent due to weak solvation.…”
Section: Resultsmentioning
confidence: 99%
“…fluoride, hydroxide etc.) thereby also rendering the Ge centre pentavalent 1113,17,22. Although the effects of the fluoride or base activation and Pd-catalyst/ligand combination on the coupling of organogermanes are still ambiguous, all but one8 of the successful examples of organogermane couplings with aryl/alkenyl halides involved activation with either base or fluoride.…”
Section: Introductionmentioning
confidence: 99%
“…), which is also rendering the Ge center pentavalent. 75,110,115,134 Even though the mechanism of fluoride/base activated Pd-catalyzed cross- …”
Section: Scheme 29 Synthesis Of 1-phenylnaphthalene Via Chlorophenylmentioning
confidence: 99%